ALDH2 mitigates LPS-induced cardiac dysfunction, inflammation, and apoptosis through the cGAS/STING pathway - Haoran Liu; Qin Hu; Ke Ren; Pengxin Wu; Yang Wang; Chuanzhu Lv (BMC, 2023)
Abstract Background Sepsis is a severe syndrome of organ dysfunction that often leads to cardiac dysfunction and endangers life. The role of mitochondrial aldehyde dehydrogenase 2 (ALDH2) in LPS-induced myocardial injury is unclear. The purpose of this study was to assess the role of ALDH2 in lipopolysaccharide (LPS)-induced myocardial injury and the regulatory mechanism and to identify potential therapeutic strategies for treating this condition. Methods An in vivo model was established by 12 h of LPS (10 mg/kg, intraperitoneal injection) stimulation, and an in vitro model was generated by stimulating H9C2 cells with LPS (10 μg/ml) for 12 h. We then used the ALDH2 activator Alda-1 and the ALDH2 inhibitor daidzin to assess their effects on LPS-induced cardiac injury. Cardiac function in mice was evaluated by using cardiac ultrasound. We used various methods to evaluate inflammation, apoptosis, and oxidative stress, including ELISA, flow cytometry, JC-1 staining, Western blotting, and DCFH-DA staining. Additionally, we used a small interfering RNA (siRNA) to knock down cyclic GMP-AMP synthase (cGAS) to further investigate the relationship between ALDH2 and cGAS in LPS-induced cardiac injury. Results LPS-induced cardiac dysfunction and increased the levels of the cardiac injury markers creatine kinase-MB (CKMB) and lactate dehydrogenase (LDH) in vivo. This change was accompanied by an increase in reactive oxygen species (ROS) levels, which exacerbated the oxidative stress response and regulated apoptosis through cleaved caspase-3, BAX, BCL-2. The expression of inflammatory cytokines such as IL-6/IL-1β/TNF-α was also upregulated. However, these effects were reversed by pretreatment with Alda-1 via the inhibition of cGAS/stimulator of interferon genes (STING) signaling pathway. Interestingly, LPS, Alda-1 and daidzin altered the activity of ALDH2 but did not regulate its protein expression. Knocking down cGAS in H9C2 cardiomyocytes alleviated LPS-induced cardiac inflammation, apoptosis, and ROS production and weakened the synergistic effect of daidzin. Conclusion We demonstrated that ALDH2 alleviated LPS-induced cardiac dysfunction, inflammation, and apoptosis through the cGAS/STING signaling pathway, thereby protecting against LPS-induced cardiac injury. This study identifies a novel therapeutic approach for treating sepsis-induced cardiomyopathy (SIC).